2020
DOI: 10.1021/jacs.0c01135
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Lattice Oxygen Binding in Ruthenium Pyrochlores to Enhance Oxygen Evolution Activity

Abstract: Ruthenium pyrochlores, that is, oxides of composition A2Ru2O7−δ, have emerged recently as state-of-the-art catalysts for the oxygen evolution reaction (OER) in acidic conditions. Here, we demonstrate that the A-site substituent in yttrium ruthenium pyrochlores Y1.8M0.2Ru2O7−δ (M = Cu, Co, Ni, Fe, Y) controls the concentration of surface oxygen vacancies (VO) in these materials whereby an increased concentration of VO sites correlates with a superior OER activity. DFT calculations rationalize these experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
246
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(250 citation statements)
references
References 41 publications
4
246
0
Order By: Relevance
“…[ 25 ] The former involves four consecutive proton and electron transfer steps with several intermediates, i.e., HO*, O*, and HOO*. [ 26 ] The corresponding intermediates structures for IrO 2 (110), La 3 IrO 7 (001), and La 3 IrO 7 (001)‐SLD are displayed at the down planes of Figures S9–S11 (Supporting Information), respectively. Whereas for the latter, the lattice oxygen atoms involve in the catalytic reaction, and ultimately being part of the gas product.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] The former involves four consecutive proton and electron transfer steps with several intermediates, i.e., HO*, O*, and HOO*. [ 26 ] The corresponding intermediates structures for IrO 2 (110), La 3 IrO 7 (001), and La 3 IrO 7 (001)‐SLD are displayed at the down planes of Figures S9–S11 (Supporting Information), respectively. Whereas for the latter, the lattice oxygen atoms involve in the catalytic reaction, and ultimately being part of the gas product.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, more complex multimetal oxides (e.g., pyrochlore A 2 Ru 2 O 7− δ , perovskite ARuO 3 ) are also emerging as potential electrocatalysts for OER. [ 141 ] Their structural diversity and compositional richness offers additional advantage to improve their catalytic activity. For example, Yang and co‐workers reported a porous Y 2 [Ru 1.6 Y 0.4 ]O 7− δ pyrochlore oxide via sol–gel method using citric acid as chelating agent.…”
Section: Porous Oer Electrocatalystsmentioning
confidence: 99%
“…[ 11a ] The authors found that partial substitution of Ru 4+ cations by the larger Y 3+ cations at B‐sites led to lattice oxygen vacancy, optimizing their energy band structure and electrocatalytic performances toward OER. A more flexible way to tailor the oxygen vacancies and improve their performance is by substituting the A‐site in porous Y 1.8 M 0.2 Ru 2 O 7− δ catalysts with transition metals (where M = Fe, Co, Ni, Cu, Y), as demonstrated by Kuznetsov et al [ 141a ] Despite these great advances, current Ru‐based OER catalysts still hardly meet the critical requirements of high activity, low cost and, especially stability to be applicable in large‐scale commercial PEM electrolyzers. Moreover, key structural subunits and reaction mechanism for most studied Ru‐catalyzed OER process are not well understood, hampering the rational modulation of Ru‐based active sites.…”
Section: Porous Oer Electrocatalystsmentioning
confidence: 99%
“…In general, the OER is considered to go through two possible pathways including the conventional adsorbate evolution mechanism (AEM) and lattice‐oxygen‐mediated mechanism (LOM). [ 79–81 ] The AEM contains four proton‐coupled electron transfer processes centered on the metal ion and the oxygen gas product is originated mainly from absorbed water molecules, as schematically shown in Figure a. Specifically, water molecules are adsorbed on the oxygen‐coordinated metal (M) sites of an electrocatalyst via an one‐electron oxidation process to form an adsorbed *OH (step 1), which is then oxidized to *O (step 2).…”
Section: Fundamentals Of Oermentioning
confidence: 99%